2011
DOI: 10.1016/j.humimm.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene methylation is associated with ethnicity, tuberculosis, and TaqI polymorphism

Abstract: The Vitamin D Receptor (VDR) gene encodes a transcription factor which, on activation by vitamin D, modulates diverse biological processes including calcium homeostasis and immune function. Genetic variation involving VDR shows striking differences in allele frequency between populations and has been associated with disease susceptibility including tuberculosis and autoimmunity, although results have often been conflicting. We hypothesized that methylation of VDR may be population specific and that the combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…Epigenetic variation in the VDR gene in different ethnic groups, arising from differential exposure to environmental factors, may influence gene regulation and therefore contribute to differential TB susceptibility. Indeed, methylation variable positions at the 3' end of VDR have been identified that are significantly correlated with ethnicity and TB status 113 .…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…Epigenetic variation in the VDR gene in different ethnic groups, arising from differential exposure to environmental factors, may influence gene regulation and therefore contribute to differential TB susceptibility. Indeed, methylation variable positions at the 3' end of VDR have been identified that are significantly correlated with ethnicity and TB status 113 .…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…Vitamin D3 reduces the pro-inflammatory response and also induces a protective response via expression of cathelicidin antimicrobial peptide (Khoo et al 2011). The activity of the vitamin D receptor gene (VDR) can be epigenetically regulated (Karlic & Varga 2011), and VDR methylation status has been shown to correlate with TB status in a human population (Andraos et al 2011). Within a CpG island at the 3 0 end of VDR, one CpG site showed significantly higher methylation in controls than in TB cases, whereas two additional CpGs showed higher methylation in TB cases than in controls.…”
Section: Patho-epigeneticsmentioning
confidence: 99%
“…Pennini et al were able to show that this chromatin remodeling effect was caused by M. tuberculosis 19K lipoprotein (LpqH) signaling via TLR2 [75,76]. Comparing the methylation statuses of CpG islands in the vitamin D receptor gene has uncovered variations at several CpG dinucleotides between different ethnic groups and between M. tuberculosis-infected and -uninfected individuals [77]. It may be interesting to speculate whether a person's CpG-methylation profile may be predictive for M. tuberculosis susceptibility, or whether different CpGmethylation profiles may have been induced by M. tuberculosis infection.…”
Section: Epigenetic Alterations Induced By Bacteria In Host Cellsmentioning
confidence: 99%
“…This is certainly an interesting field for further research (reviewed in [78]). However, as a note of caution, methylation analyses were performed from EBV-transformed lymphoblastoid cell lines obtained from the respective donors [77]. EBV by itself may contribute to an altered methylation profile in the host cell [79].…”
Section: Epigenetic Alterations Induced By Bacteria In Host Cellsmentioning
confidence: 99%